Compounded environmental health risks in mountain communities upstream of Bhumibol Dam, Thailand - Poramad Trivalairat; Isara Phiwchai; Mattika Chaichan; Krittiya Trivalairat; Narisara Sripo (PLoS ONE, 2026)
Background Indigenous, mountain communities residing upstream of Bhumibol Dam, Thailand, rely on vulnerable natural water sources for their water supply, yet remain unaware of the associated health risks. Methods This study assessed the water quality, usage patterns, and contamination pathways across six villages upstream of Bhumibol Dam to shed light on the obstacles to sustainable water security. Samples from 38 water sources of drinking and/or non-drinking water, soil, and the edible parts of crops were subjected to analyses of physical, chemical (NO 3 -N, pH), and qualitative pesticide-related variables, alongside a 6-month assessment of a community water filter system. Results Principal component analysis identified a “at-risk group” of preferred drinking water sources all exhibiting high NO 3 -N, highly alkaline pH, and substantial pesticide contamination, which was found to likely be caused by agricultural run-off. This was reinforced by the detection of pesticide residues in all soil samples and, critically, in the below-ground edible parts of crops (taro, lemongrass, arrowroot), confirming dietary exposure in the local communities. Further compounding the risks posed by the unsafe water supply, the community water filter was found to be ineffective throughout the 6-month analysis with there being no significant difference in water quality between before and after filtration. The residents’ paradoxical preference for high-risk, still water (from sand-filtered puddles) for drinking, rather than water from flowing sources, which they used only for cooking and cleaning. Conclusion Overall, these findings reveal compounded environmental health risks emerging from the convergence of mineral-rich hydrogeology, agrochemical runoff, and vulnerable water-collection behaviours. To mitigate these threats, the study suggests that decentralized water management strategies must prioritize both the implementation of advanced filtration technologies capable of mineral and chemical removal and targeted public health education to shift community reliance away from high-risk, stagnant water sources.